Prevalence of hypertension and its associated risk factors in adults: a unique study at field practice area of urban health training centre - Ingale, Abhijeet S.; Dixit, J. V. (International Journal Of Community Medicine And Public Health, 2017)
Background: The theme for World Health Day 2013 based on controlling high blood pressure, a condition which affects more than one in three adults and leads to more than nine million deaths worldwide every year. There is a felt need for the community based studies in urban and rural areas of our country with a view to determine the geographic differences in the prevalence of hypertension. The knowledge about the existing risk factors of hypertension in the local community helps in developing prevention programs tailor-made to modify behavioral changes and promoting healthy lifestyles among the target groups. The present study was undertaken to estimate the prevalence of hypertension and examine its associated risk factors in an urban area. The aim and objectives were to find out the prevalence of hypertension in the field practice area of Urban Health Training Centre and to study the risk factors associated with hypertension. Methods:A case control study after community based cross sectional study was conducted in the field practice area of Urban Health Training Centre of Government Medical College, Aurangabad, India. Subjects were examined with the help of pretested proforma. The blood pressure, weight, height of the subjects were measured and recorded according to standard protocol. Data was entered and analyzed using Epi Info statistical software. Results: 305 study subjects were examined. The overall prevalence of hypertension was 26.2%. Prevalence of hypertension was more in females 33.3% than in males 16.8% which was found to be statistically significant. All risk factors were subjected to multiple logistic regression analysis. Out of fourteen risk factors submitted for multivariate analysis, five out to be significant and independent risk factors for hypertension i.e. (higher socioeconomic status, Mixed diet, Additional dietary salt intake, <8hrs of sleep and restless sleep). Conclusions:These observations re-emphasize the need for tailor-made hypertension awareness programs. It also brings to light the need for follow-up, counselling and monitoring of hypertensive’s to reduce non-compliance to anti-hypertensive medication and lifestyle modification in urban areas.